2022
DOI: 10.1093/ejo/cjac018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clear aligners on speech: a systematic review

Abstract: Objective To assess the effect of clear aligners on the speech of patients undergoing orthodontic therapy through a systematic review of the literature. Search methods and selection criteria: The protocol of this systematic review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) CRD42021278694. An electronic search of the Scopus, Embase, Pubmed, and Web of Science databases was done for papers published between January 2000 till September 2021. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…41 It is common that during orthodontic treatment patients experience some discomfort during the adaptation process, because the devices cause pain or even interfere with tongue movements, limiting the space for tongue accommodation and therefore the patient's speech. 42,43,44 Mendes Ribeiro SM, Aragón MLSC, Espinosa DSG, Shibasaki WMM, Normando D -Orthodontic aligners: between passion and science Because they are plates that cover the tooth surface, aligners may cause discomfort to the patient in verbal articulation. 38 Several studies have reported that esthetic aligners can influence the clarity and articulation of speech, in a more pronounced way than fixed appliances.…”
Section: Can Orthodontic Treatment With Aligners Im-pact On the Oral ...mentioning
confidence: 99%
“…41 It is common that during orthodontic treatment patients experience some discomfort during the adaptation process, because the devices cause pain or even interfere with tongue movements, limiting the space for tongue accommodation and therefore the patient's speech. 42,43,44 Mendes Ribeiro SM, Aragón MLSC, Espinosa DSG, Shibasaki WMM, Normando D -Orthodontic aligners: between passion and science Because they are plates that cover the tooth surface, aligners may cause discomfort to the patient in verbal articulation. 38 Several studies have reported that esthetic aligners can influence the clarity and articulation of speech, in a more pronounced way than fixed appliances.…”
Section: Can Orthodontic Treatment With Aligners Im-pact On the Oral ...mentioning
confidence: 99%
“…Following the collection of each image, participants were asked to read a script aloud, comprising their name, age, educational qualification, and corresponding address at baseline (pre-intervention) and while wearing the clear aligners and fixed appliances, respectively. 16,17,22,23 Participants then answered the question: "Do you feel that your speech has changed?". Responses were provided on a four-point Likert scale with possible answers including: (1) "No, not at all"; (2) "Slightly";…”
Section: Speechmentioning
confidence: 99%
“…Orthodontic appliances can affect movement of the tongue and space in the oral cavity, leading to the distortion of speech 14‐16 . Prior investigations have described the effect of fixed appliances, removable appliances and orthodontic retainers on speech 14,17‐22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aligners may lead to initial speech difficulties. However, most patients adapt quickly and speech returns to normal 13 . For effective three‐dimensional tooth movements such as anterior root torque, rotation, mesio‐distal movement and intrusion or extrusion, these aligners may require adhesive composite attachments, 14 that are tooth‐colored and like the clear appliances itself almost not visible.…”
Section: Introductionmentioning
confidence: 99%